Experimental semi-device-independent tests of quantum channels. (20th May 2019) - Agresti, Iris; Poderini, Davide; Carvacho, Gonzalo; Sarra, Leopoldo; Chaves, Rafael; Buscemi, Francesco; Dall'Arno, Michele; Sciarrino, Fabio
Abstract: Quantum tomography is currently the mainly employed method to characterize a quantum system and therefore plays a fundamental role when trying to characterize the action of a particular channel. Nonetheless, quantum tomography works on the premise of a full characterization and description of the devices preparing the quantum state and realizing the measurements. Such an assumption was recently relaxed in Dall'Arno et al (arXiv:1805.01159 ) and Dall'Arno et al (2017 Proc. R. Soc. A 473 20160721), where a theoretical framework for the device-independent inference of quantum channels was developed and experimentally implemented with superconducting qubits. Here, based on such a framework, we present a complete experimental test on a photonic setup of two semi-device-independent protocols that can be employed for the validation of the tomographic reconstruction or the characterization of a given quantum channel, not relying on many assumptions on the adopted device. Our implementation paves the way to the development of new experimental methods not relying on the assumptions typically taken for granted in all the previous protocols.